2023
DOI: 10.1097/tp.0000000000004810
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Surgical-Site Infections After Liver Transplant: Does Perioperative Antibiotic Regimen Matter?

Stacey C. Rolak,
Zachary A. Yetmar,
Brian D. Lahr
et al.

Abstract: Background. Surgical-site infections (SSIs) are common in liver transplant recipients. The optimal SSI antimicrobial prophylaxis agent and duration are not established. We aimed to explore risk factors for SSIs after transplant, with a particular interest in the impact of perioperative antibiotic regimen on the development of SSIs. Methods. Retrospective study of adults undergoing liver transplant across 3 transplant programs between January 1, 2020, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…Thus, the higher risk of SSI in these patients is not unexpected. 26 Similar to other studies, we found an increased risk of SSI with posttransplant procedures 9,16 and longer operative times as has been, 4,27,28 which likely reflects increased opportunity for wound contamination, increased inflammation, and delayed healing. There may be some variability in surgical techniques that can potentially influence the rate of SSI.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Thus, the higher risk of SSI in these patients is not unexpected. 26 Similar to other studies, we found an increased risk of SSI with posttransplant procedures 9,16 and longer operative times as has been, 4,27,28 which likely reflects increased opportunity for wound contamination, increased inflammation, and delayed healing. There may be some variability in surgical techniques that can potentially influence the rate of SSI.…”
Section: Discussionsupporting
confidence: 88%
“…In this retrospective cohort study of SSI in LT recipients under a protocol of routine amoxycillin/clavulanic acid prophylaxis, the overall SSI rate was 8%, which is among the lowest rates reported in the literature from other countries. [4][5][6][7][8][9][10][11][12][13][14][15][16] Risk factors associated with SSI were Roux-en-Y hepaticojejunostomy, longer operation time, and reoperation posttransplant.…”
Section: Discussionmentioning
confidence: 99%